Will the Crisis Affect the Economic Recovery in Eastern European Countries? Evidence from Firm Level Data - Correa, Paulo; Iootty, Mariana (2012)
Two sources of growth are firm learning and innovation. Using a unique panel data for 1,686 firms in six countries (Bulgaria, Hungary, Latvia, Lithuania, Romania, and Turkey), this paper applies panel data estimators and Juhn-Murphy Pierce decomposition in order to identify the effects of the global economic crisis on sales growth of innovative and young enterprises in Eastern European countries. The results show that innovative and young firms were significantly more affected by the crisis than non innovative and older enterprises. The authors interpret these results as an indication that the achievement of pre-crisis growth rates in those countries may be difficult.